Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Pembuatan Sabun Cuci Piring Ramah Lingkungan di Desa Kuta Parit - Anita Cerahma Siregar; Siti Nur Hasanah; Hayathun Maira; Reva Kirana Putri; Khairul Ikhsan Absy; Zulpahmi Lubis (Pusat Riset dan Inovasi Nasional, 2026)
This Community Service Program (Kuliah Kerja Nyata/KKN) aimed to empower housewives through environmentally friendly dishwashing liquid production training in Kuta Parit Village, Selesai Subdistrict, Langkat Regency, responding to limited female participation in productive economic activities and increasing demand for safe household cleaning products. The program sought to enhance skills, knowledge, and economic independence among women while promoting health and environmental sustainability. A descriptive qualitative approach was applied, using observation, informal interviews, and documentation conducted during program implementation. Activity stages included education on eco-friendly soap concepts, introduction to materials and their functions, demonstrations of the production process, and hands-on practice sessions involving participants directly. KKN students served as facilitators and mentors, ensuring participants comprehended each step and were able to replicate the process independently. The results indicated that housewives successfully produced liquid dishwashing soap suitable for daily household use with acceptable quality. Beyond technical skill improvement, the program stimulated entrepreneurial motivation, strengthened confidence, and created opportunities for developing home-based microenterprises using eco-friendly products. Overall, this KKN activity contributed positively to women’s economic empowerment while supporting cleaner living practices within the community.